DIKSI DALAM KARANGAN NARASI SISWA KELAS VIII SMP NEGERI 1 PACET - Wanti Nurmalawati; Daud Pamungkas (FKIP ULM, 2012)
This article describes the ability of students of eight grade of High School 1 Pacet Cianjur 2011/2012 in the use of diction in a narrative essay. Research was carried out by using the descriptive method. Based on the results of data analysis and discussion are showed that students’ ability to write essay in terms of accuracy of the use of diction which is an average 66.36. An examination of the use of language styles, the average value obtained is 65.68 students, meanwhile, viewed from the aspect of the use of the phrase sentences in a narrative written by the average value obtained by the students is 66.36. Therefore, it can be concluded that in general the ability of students to use diction, style and expression language sentences in writing a narrative essay is generally sufficient.